2005
DOI: 10.1007/s00221-005-2321-y
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory coding in the precentral extension of area 3 in Japanese macaque monkeys; comparison with area G

Abstract: The precentral extension of area 3 as well as the transition between the frontal operculum and insula (area G) comprises the primary gustatory cortex in the subhuman primate, receiving projections from the thalamic taste relay. However, in contrast to the extensive studies that have been carried out on the latter area, only a few taste units in the former area have been recorded. To clarify gustatory coding in area 3, we investigated the taste response properties of neurons in area 3 compared with those in are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Furthermore, we have shown that temperature modulates neural responses to chemical stimulation (Breza et al, 2006). We delivered solutions to the tongue adapted to 35°C AS (Hirata et al, 2005), at low flow rate equivalent to a rat's normal rate of consumption and without confounding tactile and thermal artifacts. Under these limited conditions, the peripheral gustatory system seems to rely more on spike rate during stimulation than on spike timing for coding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have shown that temperature modulates neural responses to chemical stimulation (Breza et al, 2006). We delivered solutions to the tongue adapted to 35°C AS (Hirata et al, 2005), at low flow rate equivalent to a rat's normal rate of consumption and without confounding tactile and thermal artifacts. Under these limited conditions, the peripheral gustatory system seems to rely more on spike rate during stimulation than on spike timing for coding.…”
Section: Discussionmentioning
confidence: 99%
“…AS (Hirata et al, 2005; 15 mM NaCl, 22 mM KCl, 3 mM CaCl2, and 6 mM MgCl 2 ; pH 5.8) served as the rinse solution and solvent for the basic taste stimuli. All chemicals were reagent grade.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, anatomically, there are two “primary” thalamo-cortical gustatory projections; in terms of anterior/posterior orientation, one would be located anteriorly and one in a more middle/posterior region of the insula/operculum area. However, the latter’s existence and exact location are controversial and relatively little is known about gustatory coding in this area (but see Hirata et al 2005). Signals from the AIFO project to medial orbitofrontal cortex (mOFC) and lOFC (Baylis, et al 1995; Carmichael and Price 1995; Pritchard, et al 2005), and the amygdala (Aggleton, et al 1980; Mufson, et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Also in that study, the tongue representation was likely to receive an additive projection from the lateral surface of the frontal operculum near the lateral sulcus, although the investigators did not particularly emphasize this. This region may presumably correspond to the precentral extension of area 3, which was also implicated in gustatory function [22,23].…”
Section: Representation Of Orofacial Structures In Area 3bmentioning
confidence: 99%